Improvement of morphology, biochemical characters, and molecular changes of local upland rice cv. Sidikalang M3 generation through induction of gamma-ray irradiation - DUNAN NAIBAHO; EDISON PURBA; DIANA SOFIA HANAFIAH; SYAHBUDIN HASIBUAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Naibaho D, Purba E, Hanafiah DS, Hasibuan S. 2023. Improvement of morphology, biochemical characters, and molecular changes of local upland rice cv. Sidikalang M3 generation through induction of gamma-ray irradiation. Biodiversitas 24: 200-207. Upland rice cultivar Sidikalang is one of the local upland red rice cultivars of North Sumatra, which has the potential to be developed. However, this rice has limited planting area due to factors such as its higher plant height and long duration compared to other rice cultivars. Plant characteristics can be improved through induced mutation using gamma-ray irradiation. This study aimed to determine gamma rays' effect on changes in morphological, biochemical, and molecular characters and to obtain a superior Sidikalang cultivar mutant plant M3 generation. Observations of morphological changes were carried out quantitatively and qualitatively, biochemical analysis (amino acid content) was done using a High Performant Liquid Chromatography analyzer, and molecular analysis was performed using Random Amplified Polymorphism DNA markers. The results showed that 600 Gy gamma-ray irradiation improved quantitative morphological characters (shorter plant height, higher number of tillers and panicles, faster panicle release age) and qualitative morphological characters (flag leaf angle in dwarf mutants became upright) compared to no irradiation. 400 Gy gamma-ray irradiation also increased almost all amino acid content compared to no irradiation. The presence of polymorphic bands in the M3 generation Sidikalang cultivar mutant plant evidenced changes in morphological and biochemical characters.